Neuroaxial Versus General Anesthesia for Gynecological Surgeries: A Comparative Study - Shahneela Raza, Alina Siddiqui, Aiman Hilal, Sundas Kamran, Kiran Haseen, Muddassir Anis, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The choice of anesthetic technique in gynecological surgery significantly influences perioperative safety, postoperative recovery, and patient satisfaction. General anesthesia (GA) remains widely used due to airway control and suitability for laparoscopic procedures, while neuroaxial anesthesia (NA) offers superior analgesia and recovery benefits. Objective: To compare perioperative outcomes of neuroaxial versus general anesthesia in patients undergoing elective gynecological surgeries at a tertiary care center in Pakistan. Methods: This prospective, comparative study was conducted at the Department of Anesthesiology, Jinnah Postgraduate Medical Center, Karachi, from January to July 2023. A total of 100 female patients (ASA I–III, aged 25–60 years) were randomized into two groups: NA (n=50) and GA (n=50). Intraoperative hemodynamics, blood loss, duration of surgery, postoperative analgesia, opioid consumption, incidence of postoperative nausea and vomiting (PONV), time to ambulation, hospital stay, and patient satisfaction were recorded. Data were analyzed using SPSS v25, with p < 0.05 considered significant. Results: Baseline demographics were comparable between groups. Hypotension occurred more frequently under NA (22% vs. 8%, p=0.04), while blood loss was significantly lower (220 ± 48 mL vs. 295 ± 52 mL, p<0.001). Time to first analgesic request was longer with NA (6.2 ± 1.8 h vs. 2.4 ± 0.9 h, p<0.001), and 24-hour opioid use was reduced (12.6 ± 3.5 mg vs. 26.1 ± 5.1 mg, p<0.001). NA was associated with lower PONV rates (12% vs. 34%, p=0.01), earlier ambulation, shorter hospital stay, and higher satisfaction. Conclusion: Neuroaxial anesthesia provides superior postoperative outcomes compared to general anesthesia in open gynecological surgeries, though intraoperative hypotension is more common. Anesthetic choice should be individualized based on patient comorbidities, surgical type, and institutional resources. Keywords: Neuroaxial anesthesia; General anesthesia; Gynecological surgery; Postoperative recovery; Analgesia; Patient satisfaction.